Exploring the potential of transethosomes in therapeutic delivery: A comprehensive review - Pavani Chowdary; Ananya Padmakumar; Aravind Kumar Rengan (MedComm – Biomaterials and Applications, 2023)
Abstract The growing need for innovative drug delivery systems has led to extensive research to address the limitations associated with conventional dosage forms. Lipid nanoparticles have become prominent as frontline nanocarriers for the delivery of drugs and vaccine formulations. However, the pursuit of new materials and modifications to improve lipid nanocarrier properties remains ongoing. In this context, transethosomes have gained attention as a promising solution, offering distinct advantages over traditional formulations. Transethosomes minimize plasma fluctuations, first‐pass metabolism, organ toxicity, and poor bioavailability. This comprehensive review provides an in‐depth exploration of transethosomes, starting with an overview of the impact of formulation components on their properties and effective targeting. This article delves into the production techniques and evaluation properties employed to ensure efficient drug delivery. A significant contribution of this review lies in the analysis of various routes of administration for transethosomes, including transdermal, transvaginal, pulmonary, and ocular delivery, showcasing the versatility of transethosome‐loaded with drugs and their potential to target specific tissues to achieve controlled release. Furthermore, the potential of functionalization and photodynamic therapy approaches to enhance drug delivery efficacy are explored. Overall, this review emphasizes the significant potentiality of transethosomes as a promising drug delivery system addressing the challenges associated with conventional drug delivery approaches.